Interfacing Language Research with Policy: The Case of Language in Education in Malawi (Nordic Journal of African Studies, 2000)
This paper addresses the interaction between language research and the formulation of language policy in the education sector of Malawi. It is widely agreed in the literature of language planning that research (i.e. fact finding) is one of the most important inputs to a language policy formulation process (e.g. Rubin 1971; Chumbow 1996; Bamgbose 1991, etc.). Normally one would normally expect the fact finding process (which can be done through language surveys) to be followed by the formulation of a policy, then the implementation of the said policy, and finally an evaluation of the implemented policy. This, unfortunately, is not what normally real life situations offer. It is no surprise to hear about a policy that lacks research support. This paper highlights the relevance of research findings to the recent review of language policy in education in Malawi. Specifically, the paper reviews four sociolinguistic surveys (on Chiyao, Chitumbuka, Chilomwe and Chisena) and how they have shaped or influenced the language policy review process. These surveys were conducted by the Centre for Language Studies at the University of Malawi between 1996 and 1998, with financial and technical assistance from the German Technical Cooperation Agency (GTZ).